Estimating The Financial Repression Index for The Economy of Bangladesh: A Principal Component Analysis - Yousuf, Md (Universitas Airlangga, 2024)
Financial repression was a common practice in the past, but it became less common during the liberalization era of the 1980s and 1990s. With the rise in financial sector vulnerability following the Asian financial crisis, the Global Financial Crisis, and the COVID-19 pandemic, repressive policies have once again become popular. Bangladesh, for instance, has imposed administrative interest rate ceilings. This study aims to assess the extent of financial repression on the economy of Bangladesh, using annual time series data spanning from 1973 to 2022. An aggregate financial repression index was calculated using the principal component analytical method, including the major policy variables such as real deposit rates, interest rate restrictions, capital account restrictions, the share of state-owned commercial banks in total loans, and statutory liquidity ratio. The reliability and validity of the results were tested by comparing them with the index calculated using different policy variables. The index of financial repression indicates that Bangladesh's financial sector has undergone considerable liberalization, yet it remains subject to some degree of repression. In recent times, financial repression has intensified, particularly following the imposition of lending rate ceilings in the wake of the outbreak of the COVID-19 pandemic. Policymakers are in a position to take proper measures to liberalize the financial sector and ensure financial stability.